2021
DOI: 10.3390/molecules26113218
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Thymoquinone, an Active Compound of Nigella sativa, on Rats with Benzo(a)pyrene-Induced Lung Injury through Regulation of Oxidative Stress and Inflammation

Abstract: Benzopyrene [B(a)P] is a well-recognized environmental carcinogen, which promotes oxidative stress, inflammation, and other metabolic complications. In the current study, the therapeutic effects of thymoquinone (TQ) against B(a)P-induced lung injury in experimental rats were examined. B(a)P used at 50 mg/kg b.w. induced lung injury that was investigated via the evaluation of lipid profile, inflammatory markers, nitric oxide (NO), and malondialdehyde (MDA) levels. B(a)P also led to a decrease in superoxide dism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…With the development of phytochemistry and pharmacology research, a large number of natural products with anti-oxidant, anti-inflammatory and anti-bacterial activities have been found. Therefore, there is an increasing demand for the botanical components of traditional medicine as a source of prevention and treatment for ALI [ 28 30 ]. HKL, a natural compound extracted from Magnolia Officinalis, has been reported to have anti-oxidant and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of phytochemistry and pharmacology research, a large number of natural products with anti-oxidant, anti-inflammatory and anti-bacterial activities have been found. Therefore, there is an increasing demand for the botanical components of traditional medicine as a source of prevention and treatment for ALI [ 28 30 ]. HKL, a natural compound extracted from Magnolia Officinalis, has been reported to have anti-oxidant and anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide and associated compounds are formed by an extensive variety of residential as well as inflammatory cells in the airways [36]. A study based on animal model reported that nitric oxide level was substantially increased in the B(a)P-treated group as compared to the control group [37,38]. In the present study, it was noticed that NO levels were increased in the B(a)P-treated group animals whereas ADE treatment significantly decreases the NO levels.…”
Section: Discussionmentioning
confidence: 99%
“…in OVA-sensitized rats . THQ have also been recently reported for the protection against benzopyrene induced lung injury in rats (Al-Zohairy et al, 2021).…”
Section: Figure No 3 Blockade Of Inflammatory Pathwaysmentioning
confidence: 97%